The Direct Bonding of Metals to Ceramics and Application in Electronics. (1976) - Burgess, J. F.; Neugebauer, C. A.; Flanagan, G.; Moore, R. E.
Abstract : The direct bonding of metals to ceramics is possible utilizing a gas metal eutectic. The mechanism of direct bonding of copper foil to ceramics in a slightly oxidizing atmosphere is presented. It involves the formation of eutectic melt between copper and oxygen at a temperature slightly below the melting point of copper, which serves to bring the foil into intimate contact with the substrate. Metals to which technique is applicable include Cu, Fe, Ni, Co, Ag, Cr, Mo and Al. A brief review of other metal–ceramic bonding techniques is given for comparison. The process for fabricating direct bonded copper structures is given, and properties of the bond are discussed. The use of the directed bonding process in a number of electronic applications such as hybrid packages and power device heat sinks is indicated.